Immune-related adverse events correlate with the efficacy of PD-1 inhibitors combination therapy in advanced cholangiocarcinoma patients: A retrospective cohort study - Zhang, Yanfang; Wang, Xiaoting; Li, Yinyan; Hong, Yun; Zhao, Qingwei; Ye, Ziqi (Frontiers in Immunology, 2023)
Background: Whether irAEs can predict the efficacy of PD-1 inhibitors in cholangiocarcinoma (CCA) has not been assessed. Therefore, this study aims to investigate the correlation between irAEs and the therapeutic effect of PD-1 inhibitors combination therapy in patients with advanced CCA. Methods: All patients with CCA who were consecutively admitted to the inpatient unit of our hospital and received PD-1 inhibitors combination therapy between September 2020 and April 2022 were screened. In total, 106 patients with CCA were screened out. We then followed up these patients until October 2022. Due to perioperative use (n=28), less than 2 cycles of PD-1 inhibitor therapy (n=9), incomplete data (n=8) and no pathological report (n=2), 59 patients were included in the final analysis. The patients were divided into the irAEs cohort and the non-irAEs cohort according to whether they experienced irAEs or not. The Log-Rank test was performed to compare the difference in survival time between these two cohorts. We then applied multivariate COX regression analysis to investigate whether irAEs were independent prognostic factors for survival in patients with advanced CCA. Results: Finally, 32 patients were included in the irAEs cohort and 27 patients in the non-irAEs cohort. A total of 32 patients (54.2%) had any-grade irAEs, of which 4 patients (6.8%) had grade 3-4 irAEs. The most common irAEs were thyroid toxicity (30.5%) and dermatologic toxicity (30.5%). There were no notable differences in demographics and clinical characteristics between the irAEs and non-irAEs cohorts, except for total bilirubin level (P=0.026) and relapse (P=0.016). The disease control rate (DCR) in the irAEs cohort was higher than in the non-irAEs cohort (90.6% vs 70.4%, P=0.047). Median overall survival (OS) and median progression-free survival (PFS) were better in the irAEs cohort than in the non-irAEs cohort (OS: 21.2 vs 10.0 months, P<0.001; PFS: 9.0 vs 4.4 months, P=0.003). Multivariate COX regression analysis showed that irAEs were independent prognostic factors for OS and PFS (OS: HR=0.133, 95% CI:0.039-0.452, P=0.001; PFS: HR=0.435, 95% CI:0.202-0.934, P=0.033). Conclusion: IrAEs correlated with improved DCR, OS, and PFS in advanced CCA patients receiving PD-1 inhibitors combination therapy.